Adubação de sistemas: indicadores químicos e biológicos para determinação da ocorrência de "solo saudável" em integração lavoura pecuária - Zortéa, Talyta (2021)
The integrated systems of agricultural production together with practices of system-level fertilization, can promote an increase in the occurrence of healthy soils and consequently improve and the productivity of a system. Some of the indicators for evaluating changes in the characteristics of a healthy soil, can be: carbon and total nitrogen of the soil, CO2 flow after rehydration of dry soils, inorganic N and water-stable aggregates. The objective of this work was to evaluate the occurrence of "healthy soil" promoted by the interaction between the application of nitrogen fertilization in different cultivation phases and grazing pressures in a system of livestock crop integration, through the changes observed in the organic matter of the soil (C and N) and its particulate fraction, ammoniacal nitrogen and soil nitrate contents as well as the microbiological parameters of the soil. The present work was carried out in an agricultural property located in Abelardo Luz - SC, in the agricultural year of 2017/2018, consisting of the succession of two crops in the system of livestock crop integration, title them in phases, Phase I = pasture, Phase II = grains (corn). The experimental design was a randomized block with three replications, distributed in a factorial scheme with two factors, the first factor being Nitrogen fertilization time: N applied to pasture (N-Pasture) and N applied to grain culture (N-Grains), at a dose of 200 kg of N ha-1, in a single application. The second factor was the Pasture Height, characterized by two pasture management heights (High Height and Low Height). Significant increases were observed in the stocks of C and N at a depth of 0-10 cm from the soil, after six years of soil conducted in the livestock crop integration. Only in the treatment with low grazing intensity and without N-fertilization on pasture showed reductions in the levels of C and N. The C content of the particulate organic matter (POC) fraction was affected mainly by the height of the pasture, where the high pasture height greater accumulations of C were observed in this fraction, this condition was determined by the intrinsic characteristics of the pasture (higher C/N ratio) which reduced the decomposition speed of this fraction. The application of nitrogen fertilization during the grazing phase was able to sustain high levels of N-nitrate at a depth of 0-5 cm during the cultivation of corn. No evidence of nitrate leaching was observed, up to a depth of 40 cm, caused by the application of a single dose. The presence of a large amount of straw on the soil at the end of grazing stimulated the flow of CO2 at 3 days of incubation. The parcels that received N during the cultivation of the pasture (N-pasture) showed greater microbial activity as well as higher carbon content in the biomass at the end of the corn cultivation period. It is concluded that the N applied to the soil during the cultivation of oats is able to remain in the system, immobilized in the microbial biomass, and present its residual effect in the cultivation of the subsequent corn mainly in the superficial layer of the soil. The application of nitrogen in the pasture phase in a crop-livestock integration system conducted under no-tillage system enhanced the use of inputs applied in only one phase of the experiment conduction and even so promoted an increase in the accumulation of C and N and avoided losses of nutrients by the leaching process.